2010
DOI: 10.1051/0004-6361/201014504
|View full text |Cite
|
Sign up to set email alerts
|

Application of the theory of damping of kink oscillations by radiative cooling of coronal loop plasma

Abstract: Aims. We present here a first comparative study between the observed damping of numerous fast kink oscillations and the theoretical model of their damping due to the cooling of coronal loops. The theory of damping of kink oscillations due to radiation of the solar plasma with a temporally varying background is applied here to all known cases of coronal kink oscillations. Methods. A recent dynamic model of cooling coronal loops predicts that transverse oscillations of such loops could be significantly damped du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Hence, it seems to be a viable assumption that while the plasma inside the loop is cooling, the temperature of the plasma outside the loop remains constant. Following Aschwanden & Terradas (2008) and Morton & Erdélyi (2010), we approximate the temperature evolution inside the loop by an exponentially decaying function,…”
Section: Effect Of Cooling On the Kink Oscillations Of Coronal Magnetmentioning
confidence: 99%
“…Hence, it seems to be a viable assumption that while the plasma inside the loop is cooling, the temperature of the plasma outside the loop remains constant. Following Aschwanden & Terradas (2008) and Morton & Erdélyi (2010), we approximate the temperature evolution inside the loop by an exponentially decaying function,…”
Section: Effect Of Cooling On the Kink Oscillations Of Coronal Magnetmentioning
confidence: 99%
“…Similar to Paper I we also assume that the plasma temperature outside the loop, T 0 , does not change with time, while it decreases inside the loop due to the radiative cooling. Following Aschwanden & Terradas (2008) and Morton & Erdélyi (2010) we approximate the temperature evolution inside the loop by an exponentially decaying function,…”
Section: Kink Oscillations Of Cooling Coronal Loopsmentioning
confidence: 99%
“…They reported a 35% decrease in the oscillation period in the event reported by Nakariakov et al (1999). The problem of the period decrease has been also addressed by Morton & Erdélyi (2010) who found that the analytical profile with increasing frequency fits better the observational data than the profile with the constant frequency. On the other hand, the period decrease has not been found in any other papers analyzing observations of coronal loop kink oscillations, including the paper by Aschwanden & Schrijver (2011), which is not surprising at all.…”
Section: Kink Oscillations Of Cooling Coronal Loopsmentioning
confidence: 99%
“…As the majority of modelling of coronal loop oscillations is conducted using static background parameters (e.g., temperature, density), one opportunity to consider additional physics theoretically is to incorporate some form of time-dependence (see, for example, Dymova and Ruderman 2005;Al-Ghafri and Erdélyi 2013;Erdélyi et al 2014). Morton and Erdélyi [2009] considered the damping of coronal loops due to cooling through time and found, that for typical oscillatory periods, cooling could play a key role in explaining observed damping profiles (this was shown further in Morton and Erdélyi 2010). The idea that amplification of coronal loop oscillations could occur due to cooling within coronal loops that contained flow was first suggested by Ruderman [2011a].…”
Section: Introductionmentioning
confidence: 98%